Mekanisme Pengawasan Dewan Pengawas SharÃ®âah terhadap Bank Pembangunan Daerah (BPD) Daerah Istimewa Yogyakarta - el Qori, Dani (MarÃƒÂ¢ji`: Jurnal Ilmu Keislaman, 2014)
This study attempts to reveal the mechanism of supervision conducted by the Syariah Supervisory Board (Dewan Pengawas Syariah /DPS) in BPD DIY Syariah, roles and tasks of the DPS in BPD DIY Syariah, and the implementation of PBI No. 11/33/PBI/2009, in particular regarding the duties and responsibilities of DPS. This research is a field research that uses descriptive analysis approach. Data were collected through interviews, observation, and literature or document review. This study indicates that the control mechanisms of the DPS in BPD DIY Syariah is by using the method of sample tests carried out either weekly or biannually. To strengthen the results of the sample test, the DPS also asks for information from the staff of BPD DIY Syariah, particularly with respect to operational bank products. Samples of transaction documents are analyzed for conformance with the principles of SharÃ®âah. In general, the DPS in BPD DIY Syariah has implemented his duties and responsibilities in accordance with PBI No. 11/33/PBI/2009. However, the DPS cannot run control management well, especially in terms of planning and supervision.